Marginal voices in Chimamanda Ngozi Adichie’s "Americanah" - Lombardo, Andrea Laura (2019)
This study aims to examine the marginal voices that are present in the novel "Americanah" (2013) by Nigerian author Chimamanda Ngozi Adichie, representative of the black female literary writers with African roots who write in English (Koziel, 2015). Adichie’s hybrid, creative and interlingual use of language exhibits aspects of form and content that are particularly significant to the trace of minor voices being heard in the text. In this respect and within the framework of minor literatures as defined by Deleuze and Guattari ([1975] 1986) and revisited by Bensmaïa (2017) and the contributions of postcolonial theory (Ashcroft et al., [1989] 2002; Mwangi, 2009), the Author discursive image or "ethos" (Amossy, 1999, 2009, 2012) is constructed around transcultural writing strategies (Murphy, 2017) which delineate and challenge the configuration of a homogeneous identity, a unique language and a uniform culture. Thus, these minor marginal voices (both those of the black Nigerian communities and those of transnational black backgrounds) are revealed in the migrant processes of re-localization of cultural-linguistic spaces, i.e. in-between two languages (English and Igbo, in our case) and two cultures (Western/ American culture and African/Nigerian culture). Hence, diaspora negotiates identity in transnational spaces either in a third-code language or in an identity transformation (Mohanty, 2003; Mishra, 2006; Koziel, 2015). In this way, the translated being turns out to be the true expression of his/ her own liberty.